Pharmacotherapeutic Analysis and Prescription Pattern of ‎Antihypertensive Drugs Dispensed at Community Pharmacies in Palestine‎ - Waleed Sweileh (My University, 2003)
The objective of this study is to explore the influence of current therapeutic recommendations on the prescribing trends of anti-hypertensive drugs in general medical practice in Palestine. Five hundred and seventy four anti-hypertensive prescriptions were analyzed. The percentage of mono-therapy prescriptions was 48.25% and that for combinational therapy prescriptions was 51.75%. Among the mono-therapy prescriptions, b- blockers were the most commonly prescribed, while diuretics were under-utilized. Inappropriate dose strength of atenolol was seen in mono-therapy prescriptions. Expensive and newer angiotensin converting enzyme inhibitor drugs (ACE-I) and calcium channel blocking drugs (CCB) were frequently seen in mono therapy prescriptions. Among the combinational therapy, the b-blockers / diuretics was most common. Irrational combinational therapy of b-blockers / ACE-I was noticed. Use of modern and new CCB, ACE-I and angiotensin II type 1 receptor antagonists (AT1-RA) was seen in both mono therapy and combinational therapy. The overuse of nonprefered drugs and the under-use of prefered medications is indicative that education of JNC VI guidelines for physicians and health professionals in Palestine is needed.